STUDI KOMPARATIF TENTANG HUKUM EKONOMI SYARIAH DAN HUKUM EKONOMI KONVENSIONAL: SEBUAH PERBANDINGAN METODOLOGI DAN PRAKTIK - Gani, Ahmad Abdul (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
In the era of globalization and technological advances, an understanding of economic law, both sharia and conventional, is becoming increasingly important. This article examines the comparison between Islamic economic law and conventional economic law in the context of methodology and practice. This study uses a descriptive and comparative analysis approach by reviewing various literature and previous research. The results of the study show that although they have different principles and principles, these two legal systems have several things in common, such as a focus on economic stability and consumer protection. However, the sharia economic law system emphasizes the aspects of fairness, transparency and risk sharing, while conventional economic law tends to focus on the aspects of profit and risk management. This article also shows that in some cases, the principles of Islamic economic law can provide innovative and sustainable alternative solutions to contemporary economic challenges. The conclusion of this article emphasizes the importance of better understanding and dialogue between the two legal systems to achieve the goal of a more inclusive and sustainable economy.